Expression of hepatocyte growth factor receptor (c-met) mRNA in primary cultures of human hepatocytes - Hirono, S (1995)
Aim—To investigate the regulation of hepatocyte growth factor (HGF) receptor (c-met) gene expression in isolated primary human hepatocytes. Methods—Primary hepatocytes were maintained in monolayer culture for up to 72 hours in serum-free medium. They were treated with growth factors and the level of HGF, c-met and reduced glyceraldehyde-phosphate dehydrogenase mRNA expression determined by northern blot analysis. Results—Hepatocytes expressed a single 9 kilobase c-met gene transcript whilst HGF mRNA analysis was negative. Addition of HGF and epidermal growth factor, both potent mitogens for human hepatocytes, enhanced c-met mRNA expression approximately twofold within 24 hours, after which levels returned to normal. In non-growth factor treated cells, transforming growth factor-β (TGFβ) had little effect upon c-met mRNA levels. However, TGFβ inhibited the HGF induced increase in c-met mRNA levels. Conclusions—These results indicate that hepatocytes which proliferate in response to HGF demonstrate levels of c-met mRNA which are subject to growth factor modulation and suggest an important means of growth regulatory control.